Catalytic wet peroxide oxidation of highly concentrated 4-nitrophenol solutions using metal-free graphene-based materials - Ribeiro, Rui (2014)
Graphene and its derivatives possess unique electronic, optical, thermal and mechanical properties that fascinated the scientific community in the last few years [1, 2]. At the same time, different carbon materials have been reported as metal-free catalysts for the catalytic wet peroxide oxidation (CWPO) of toxic and bio-recalcitrant organic pollutants, even when operating at high pollutant loads (5 g L-1) [3].